QUALITY OF PUBLIC SERVICES BY NORTH KOLAKA SOCIAL SERVICE: SOCIAL ASSISTANCE IN LAMBAI - Firdaus, Firdaus; Delviana, Ayu; Arafat, Arafat; Ribcalia Septiana, Anis (Gema Kampus IISIP YAPIS Biak, 2025)
Social assistance services at the Social Service Office of North Kolaka Regency are still not operating effectively, with the main issues identified being the low quality of information provided, limited facilities, and the lack of employees' ability to utilize technology. Some employees still face difficulties in operating computers due to insufficient training and understanding of technology. This situation results in slow and inefficient service processes, negatively impacting community satisfaction levels. This study aims to assess the quality of public services, particularly in the context of social assistance to the needy in the Lambai District. The research findings indicate the presence of obstacles, such as a limited number of field officers and slow data collection conducted by Social Service employees for the underprivileged community. Nevertheless, the service process has been reasonably effective, especially for vulnerable groups such as persons with disabilities, the elderly, disaster victims, and extremely poor communities. Assistance is provided based on the Integrated Social Welfare Data (DTKS) and field assessments to ensure target accuracy. Furthermore, the community understands their rights and obligations and actively participates in the service process alongside village officials and social companions, with services delivered in a friendly, fair, and non-discriminatory manner. Therefore, it is advisable for the Social Service Office to intensify outreach and educational initiatives concerning the service procedures, especially the verification and reapplication stages, in order to improve public comprehension and foster greater engagement in social assistance programs.